Solar Elastosis in Its Papular Form: Uncommon, Mistakable - Jun Khee Heng; Derrick Chen Wee Aw; Kong Bing Tan (Karger Publishers, 2014)
Solar elastosis is a degenerative condition of elastic tissue in the dermis due to prolonged sun exposure. There are a variety of clinical manifestations of solar elastosis. In its most common form, solar elastosis manifests as yellow, thickened, coarsely wrinkled skin. We report two uncommon cases of severe solar elastosis with a papular morphology. Its presentation can closely mimic a host of cutaneous disorders and thus, although it is helpful to be cognizant of this entity, it is still crucial to biopsy these lesions to avoid missing a more sinister condition.